Inside Cover: IR Spectrum and Structure of a Protonated Disilane: Probing the SiHSi Proton Bridge (Angew. Chem. Int. Ed. 5/2013). Issue 5 (16th January 2013) - Savoca, Marco; Langer, Judith; Dopfer, Otto
<x xml:space="preserve">Abstract</x> The IR spectrum of Si2H7+ provides the first spectroscopic characterization of the geometric and electronic structure of this polysilane cation. In their Communication on page 1568 ff., O. Dopfer et al. give direct evidence for a nonlinear SiHSi proton bridge with a three‐center two‐electron bond. The IR fingerprint may be used for its identification in silane plasmas, including the interstellar medium (copyright ESO/F. Meynadier, M. Heydari‐Malayerie, N. R. Walborn).<boxed-text content-type="graphic" position="anchor" orientation="portrait"> </boxed-text>